Suspended particle destabilization in retained urban stormwater as a function of coagulant dosage and redox conditions - Sansalone, John J.; Kim, Jong-Yeop (Water research (Oxford), 2008)
Source area runoff entrains a hetero-disperse particle size distribution (PSD). When retained for clarification, larger sediment and settleable particles are mainly influenced by gravitational forces, while the suspended particles, in particular the clay-size particles, are subject to coagulation phenomena. Such phenomena occur in untreated runoff as well as runoff treated with a coagulant, albeit to differing rates and extents. Runoff PSDs and water chemistry indices including zeta potential ( ξ) are potentially modified during inter-event stormwater retention in best management practices (BMPs). This study examined ξ of clay-size particles (<2 μm) in retained runoff, captured from an instrumented watershed, subject to batch coagulation and variable redox conditions. Separate parallel tests were also conducted with wastewater. Significant turbidity, particle mass (measured as total suspended solids (TSS)) and volume concentration (as total volume concentration (TVC)) reduction generated by alum and ferric chloride consistently occurred at a ξ in the range of −15 to about −10 mV. Alum addition produced a charge reversal at dosing above 60 mg/L (18×10 −5 M) while ferric chloride did not reverse charge. With respect to turbidity and TSS reductions, alum outperformed ferric chloride, without the need for pH control. While ξ illustrated no clear trend during aerobic retention, anoxic retention resulted in a trend for ξ approaching the isoelectric point. The decrease in negative ξ towards the isoelectric point appears to be a result of the coupled pH depression under reductive conditions and an increase in conductivity. Results have significant implications for BMPs that retain runoff between events.